LANSKAP PERKEBUNAN TEMBAKAU KEBONARUM DAN GAYAMPRIT KABUPATEN KLATEN - Galih Sekar Jati Nagari (Berkala Arkeologi, 2018)
Abstract Klaten is a region in Surakarta residency in 18-20th century during Colonial era. It held an important role in the economy of Surakarta region during that period. Klaten became area with the highest plantation productivity in Surakarta. Several plantation companies were established in Klaten, including sugar industries, indigo plantations, and tobacco plantations. Today, several plantation infrastructures can be observed, and its historical background can be traced well, but researches about Klaten Colonial industries are seldom. There are operating tobacco plantations in Klaten Regency, located in Kebonarum and Gayamprit. Plantation area in Kebonarum and Gayamprit is used as research material. Survey and historical approach are used in this research. This project aims to explore the important role of Colonial plantations in rural societies, through archaeological environment phenomenon and its history. The existence of plantations in Klaten rural areas was able to offer social change to the societies in Colonial era.